2020
DOI: 10.18805/ajdfr.dr-1547
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fruit Bagging with Different Coloured Non-woven Polypropylene Bags on Yield Attributes in Grapes

Abstract: Background: Grape is one of the important cash crops cultivated in India. The grape bunches during growth stages are adversely affected by various biotic and abiotic factors which in turn affects the yield and quality. In addition, high usage of agrochemicals in grape cultivation increased concern over pesticide residues among consumers. Therefore, an alternative technique of fruit bagging to enhance the yield and quality as well as to minimize pest and disease infestation is emphasized. Bagging of grape bunch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Quite recently, Pisciotta et al [98] reported that a bagging treatment is effective both in red and white table grapes; in fact, bagging led to a yield increase for the white varieties "Italia" and "Regal Seedless" and also for the red cultivar "Autumn Royal", whose bunches, although of a slightly lighter skin color, showed in-creased color uniformity, reduced color variation and improved berry hardness. Furthermore, the bagging with white color non-woven polypropylene of "Muscat Hamburg", which is a black berried grape, suitable both for wine-making and as table grape, determined a higher yield in terms of bunch weight, berry weight and wine yield [99].…”
Section: Bagging and The Color Of Fruitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite recently, Pisciotta et al [98] reported that a bagging treatment is effective both in red and white table grapes; in fact, bagging led to a yield increase for the white varieties "Italia" and "Regal Seedless" and also for the red cultivar "Autumn Royal", whose bunches, although of a slightly lighter skin color, showed in-creased color uniformity, reduced color variation and improved berry hardness. Furthermore, the bagging with white color non-woven polypropylene of "Muscat Hamburg", which is a black berried grape, suitable both for wine-making and as table grape, determined a higher yield in terms of bunch weight, berry weight and wine yield [99].…”
Section: Bagging and The Color Of Fruitsmentioning
confidence: 99%
“…after fruit set non-woven UV stabilized polypropylene of different colors improved yield (both in summer and winter season) [99] Grape "Kyoho"…”
Section: Crop/cultivarmentioning
confidence: 99%
“…In Japan, this technology has long been applied to the production of pears [23], apples [24] and peaches [25]. In India, this technology has been applied to the production of apples [26,27], pomegranates [28,29], guavas [30], grapes [31] and litchis [32]. In the United States, this technology is widely used in the production of apples [33] and peaches [34,35].…”
Section: Overview Of Fruit Bagging Technologymentioning
confidence: 99%
“…Among them, as shown in Figure 7b, the applied nylon fruit bags are mainly white and black [79]. As shown in Figure 7c, the non-woven fruit bags are mainly white and green [31,80]. At the same time, these two types of fruit bags have been widely used in bagging fruit such as dragon fruits [60], grapes [11], mangos [53] and litchis [61] in southern China due to their advantages in ventilation and insect prevention.…”
Section: Other Types Of Fruit Bagsmentioning
confidence: 99%